2002
DOI: 10.1124/jpet.102.045856
|View full text |Cite
|
Sign up to set email alerts
|

Active Transport of High-Affinity Choline and Nicotine Analogs into the Central Nervous System by the Blood-Brain Barrier Choline Transporter

Abstract: Cigarette smoking is strongly implicated in the development of cardiovascular disorders. Recently identified nicotinium analogs may have therapeutic benefit as smoking cessation therapies but may have restricted entry into the central nervous system by the blood-brain barrier (BBB) due to their physicochemical properties. Using the in situ perfusion technique, lobeline, choline, and nicotinium analogs were evaluated for binding to the BBB choline transporter. Calculated apparent K i values for the choline tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 28 publications
1
41
0
3
Order By: Relevance
“…This fact suggests that this transporter is not saturated under physiological condition and may deliver other compounds to the brain. Actually, the BBB choline transporter has been also reported to play an important role in the brain uptake of other organic cationic compounds such as eperisone, derivatives of lobeline, isoarecolone, and nicotine (Kang et al, 1990;Metting et al, 1998;Allen et al, 2003). Therefore, the BBB choline transporter has been suggested to be suitable as one of drug delivery vectors for cationic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This fact suggests that this transporter is not saturated under physiological condition and may deliver other compounds to the brain. Actually, the BBB choline transporter has been also reported to play an important role in the brain uptake of other organic cationic compounds such as eperisone, derivatives of lobeline, isoarecolone, and nicotine (Kang et al, 1990;Metting et al, 1998;Allen et al, 2003). Therefore, the BBB choline transporter has been suggested to be suitable as one of drug delivery vectors for cationic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, following repeated treatment with nicotine, bPiDDB seems to penetrate the BBB at concentrations that block the centrally mediated effects of nicotine. Furthermore, we have shown previously that bPiDDB has high affinity for the BBB choline transporter , a known vector for CNS penetration of cationic molecules (Allen and Smith, 2001;Lockman and Allen, 2002;Allen et al, 2003).…”
mentioning
confidence: 99%
“…However, in our recent studies, the blood-brain barrier choline transporter was shown to bind to a large number of structurally-related quaternary ammonium cations, and this transporter was shown to facilitate the brain bioavailability of at least two of these charged molecules, specifically, the monocationic quaternary ammonium compound, Noctylnicotinium iodide (NONI), and the bis-quaternary ammonium compound, bPiDDB [84]. Thus, while affinity does not equate to transport across the blood-brain barrier choline transporter, affinity coupled with demonstrated CNS activity (i.e., the current results from behavioral studies) suggest that TMPD utilizes the blood-brain barrier choline transporter as a vector to access the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Future kinetic analyses will be performed using radiolabelled-TMPD to directly determine the brain bioavailability of TMPD. In this respect, given that TMPD had a 2-fold higher affinity for the blood-brain barrier choline transporter, and that choline plasma levels are only about 25% of the K m of the blood-brain barrier choline transporter, the carrier has the capacity to transport TMPD without interrupting the supply of choline to the brain [84].…”
Section: Discussionmentioning
confidence: 99%